Pengembangan Pendidikan Karakter Positif Untuk Meningkatkan Penerimaan Diri Remaja di Lingkungan Sosial Pada Siswa Sekolah Menengah Pertama - Itryah Itryah; Dewi Septaliza; Aldi Anugrah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a positive character education module to improve adolescents’ social acceptance in school environments. The method employed was Research and Development using the 4-D model consisting of define, design, develop, and disseminate stages, although this study was limited to the develop stage. The research subjects were junior high school students. The instruments used were the Child Behavior Checklist (CBCL) and questionnaires to identify adolescent behavioral characteristics as the basis for module development. The results indicated that the developed positive character education module was designed based on adolescent developmental needs and students’ behavioral characteristics, including anxiety, withdrawal, somatic complaints, social problems, attention issues, rule-breaking, and aggressive behavior. The module serves as a learning medium to support positive character strengthening and adolescents’ social acceptance. In conclusion, the developed positive character education module is feasible to support positive character formation and improve adolescents’ social acceptance. Keywords: Adolescents, Character Education, Positive Character, Social Acceptance